Prognostic value of the HALP score in metastatic castration-resistant prostate cancer: an analysis combined with time to castration resistance - Gökmen, İvo; Demir, Nazan; Peker, Pınar; Özcan, Erkan; Akgül, Fahri; Bayrakçı, İsmail; Divriklioğlu, Didem; Erdoğan, Bülent; Topaloğlu, Sernaz; Hacıoğlu, Muhammet Bekir (Frontiers in Oncology, 2024)
ObjectiveThe aim of our study was to assess the impact of the combination of HALP score with TTCR score on OS and PFS in PC patients who developed castration resistance.Patients and methodsThe study enrolled 152 patients with metastatic disease who had received either ARTAs or docetaxel as first-line treatment. The median cut-off was 30.83 months for the HALP score and 16.1 months for TTCR determined by ROC analysis. Based on these cut-off values, patients were categorized into low-high HALP score and TTCR <16.1 months-TTCR ≥16.1 months groups. The combination of HALP score and TTCR was then stratified by risk into three new groups: Factor 0, Factor 1, and Factor 2.ResultsPFS was significantly shorter in the TTCR <16.1 months group compared to the TTCR ≥16.1 months group, as well as in the low-HALP score group compared to the high-HALP score group. Furthermore, as the number of factors increased, a significant increase in OS and PFS was observed in the groups formed by the combination of HALP score and TTCR.ConclusionWe have validated the predictive capability of combining low HALP score (<30.38) and short TTCR (<16.1 months) parameters in estimating the OS and PFS durations of mCRPC patients, both recognized as unfavorable prognostic indicators.